"Breaking the word" and "sticking with the picture": Critical literacy education of US immigrant youth with graphic novels. Issue 1 (3rd May 2016) - Park, Jie Y.
Abstract : Purpose: This paper aims to illustrate how first-generation immigrant youth who are English language learners respond to graphic novels and what literacies they acquire from reading and discussing graphic texts. Design/methodology/approach: This paper is based on qualitative discourse data collected from an afterschool program with five high-school-aged English-language learners and their teacher. The afterschool program is centered on reading and discussing graphic novels. Findings: Transcript analysis showed that the girls, even while working to "break" the written code, were engaged in critical analysis. In other words, English learners' struggles to decode the words did not hinder them in assuming the role of a text analyst, and in questioning the creator's message, purposes and worldviews. Research limitations/implications: This paper, which draws on an approach wherein the researcher pays close attention to immigrant youth as language users and meaning makers, can inform the methodologies of literacy and language researchers. Practical implications: The paper can also inform the work of educators who are interested in pedagogical supports – texts and practices – that promote powerful language and literacy. Originality/value: This paper is timely, given not only the challenges and possibilities associated with educating recent-arrival immigrant youth and English-language learners, but also the growing interest by language and literacy educators in the role of multimodal texts for developing multiple and critical literacies of all students.